2010
DOI: 10.1002/sia.3357
|View full text |Cite
|
Sign up to set email alerts
|

Influence of active layer thickness and annealing in zinc oxide TFT grown by atomic layer deposition

Abstract: aWe utilized atomic layer deposition (ALD) for the growth of the ZnO channel layers in the oxide thin-film-transistors (TFTs) with a bottom-gate structure using a SiO 2 /p-Si substrate. For fundamental study, the effect of the channel thickness and thermal treatment on the TFT performance was investigated. The growth modes for the ALD-grown ZnO layer changed from island growth to layer-by-layer growth at thicknesses of >7.5 nm with highly resistive properties. A channel thickness of 17 nm resulted in good TFT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…So, this may be related to the lack of chemical bonding sites such as O-H groups on the surface of SiO 2 34. In previous study3536, it is reported that more ALD cycles are required for full coverage of the ZnO layer on SiO 2 surface, due to deficient O-H groups on the surface of the SiO 2 . In general, it is well known that the surface of untreated Al 2 O 3 is hydrophilic due to an abundance of hydroxyl (OH − ) groups.…”
Section: Resultsmentioning
confidence: 98%
“…So, this may be related to the lack of chemical bonding sites such as O-H groups on the surface of SiO 2 34. In previous study3536, it is reported that more ALD cycles are required for full coverage of the ZnO layer on SiO 2 surface, due to deficient O-H groups on the surface of the SiO 2 . In general, it is well known that the surface of untreated Al 2 O 3 is hydrophilic due to an abundance of hydroxyl (OH − ) groups.…”
Section: Resultsmentioning
confidence: 98%
“…On one hand, oxygen vacancy defects with high coordination or that are negatively charged serve as shallow donors that donate free carriers to the conduction band and contribute to the conduction of the film, which are favorable for some applications such as transparent conductive oxide film. However, oxygen vacancy defects need to be carefully controlled in some applications such as TFTs, where the free carrier concentration should be controlled at a low level so that they can be depleted to achieve the off-state of the TFTs [18][19][20]. On the other hand, oxygen vacancy defects with low coordination, that are neutrally or positively charged, serve as deep trap states in the band gap.…”
Section: Introductionmentioning
confidence: 99%
“…It is well‐known that the electrical performances of TFT devices, including the V th , μ FE , and I On/Off ratio, strongly depend on the electrical properties of the channel layers. In this study, the as‐grown ZnO thin film has a carrier density of 8 × 10 18 cm −3 and an electrical conductivity of 1.25 × 10 2 [Ω∙cm] −1 before postannealing, which is too high to be used as a channel layer in an oxide TFT . The high background carrier density in the ZnO layers is related to oxygen vacancies and can be artificially controlled by post‐thermal treatment at oxygen ambient.…”
Section: Resultsmentioning
confidence: 99%